The cultural impact of workflow management systems in the financial services sector - Neil Doherty; Ivor Perry (2001)
The implementation of information systems is increasingly resulting in significant changes to the host organisation’s culture. In particular, the workflow management system (WFMS) is one new technology that, because of its tendency to have a direct impact on the organisation and execution of work, has the potential to significantly modify an organisation’s culture. This qualitative research investigates the nature of the relationship between WFMS and organisational culture, in the UK financial services sector The research concludes that WFMS have the potential to modify culture in a positive way by improving the organisations customer orientation, flexibility and quality focus.